The pandemic in post-modernity and its implications for the concept of love (Quaestiones Disputatae: temas en debate, 2022)
This reflection article presents the theme of love in the pandemic postmodern scenario, arguing the transformation of the concept of love according to the particularities that the containment measures for the Covid-19 have generated, understanding that the confinement and quarantines have been realities understood from particular experiences permeated by the economy, social reality, spiritual or philosophical reflection on the meaning of life or the impacts on mental health. The article offers an analytical reflection from a diversity of positions that help to understand the phenomenon of the pandemic in the postmodern scenario and the way in which it has transformed the concept of love. Thus, elements are collected that allow us to understand particularities of the Covid-19 pandemic in postmodernity, showing the diversity of experiences from which, it was signified and the way in which these meanings give particular meanings to the reality that this event represented for the humanity
Keywords: Pandemic, affectivity, social transformation, social change, love